PENINGKATAN PROSES DAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL NUMBER HEAD TOGETHER PADA PEMBELAJARAN MATEMATIKA DIKELAS VI SDN 128/II PASIR PUTIH - Timang Neelam Saty; avana nurlev; dhini mufti (STKIP Subang, 2025)
The study of this research was to enhance mathematical learning processes and academic performance among sixth-grade pupils at SD Negeri 128/II Pasir Putih by applying the Number Head Together cooperative learning approach. The research motivation stemmed from poor mathematical performance among learners, with roughly 70% of pupils failing to achieve the Minimum Mastery Criteria. These challenges resulted from the extensive reliance on traditional instructional approaches, insufficient use of tangible educational resources including visual materials, and limited student engagement in mathematical learning activities, particularly when grasping abstract mathematical concepts such as fractions and decimals.The research utilized a Classroom Action Research methodology comprising two cycles, with each cycle containing two sessions. Information was gathered using classroom observations of instructional activities, student assignment sheets, and academic performance assessments. The data examination showed substantial enhancement in both instructional processes and mathematical performance following the adoption of the NHT approach. During the initial cycle, student proficiency rates achieved 59%, subsequently rising to 81% in the following cycle, demonstrating that the instruction had reached collective mastery standards. The instructional process similarly advanced from 65% effectiveness in the first session of cycle I to 93% in the final session of cycle II, as observed in both educator and student performance.The research determined that the NHT instructional model successfully promotes student engagement, teamwork, learning enthusiasm, and comprehension of mathematical principles related to fractions and decimals. Consequently, the NHT approach represents an effective alternative instructional method for elementary mathematics education to elevate learning quality and student academic success.